Self Actualization in a Novel by Andrea Hirata’s Laskar Pelangi - Dyah Puji Rahayu; Setya Yuwana; Roni Roni (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The purpose of this research is to describe the fulfillment of needs as a process of self-actualization of the main characters who support in the form of business, difficulties, and achievement.This research is a qualitative research with descriptive method. The data used in this study is verbal, in the form of words, phrases or sentences obtained from research data sources, namely the text of the novel Laskar Pelangi by Andrea Hirata.The research results show that Ikal was able to actualize himself by getting a scholarship to study abroad after going through various failures such as being a badminton athlete and writer. Previously, Ikal succeeded in fulfilling the first stage, namely his physiological needs by working as a letter sorter. Second, the security needs achieved by relying on his own abilities so that Ikal feels safe when doing his work even though he must have discrimination from the head of the expedition.Third, the attainment of love needs and the existence achieved in a way loving his childhood friend, the love of his best friend, and family even by making various kinds of sacrifice. Fourth, Ikal can achieve the appreciation needs by equip himself with some knowledge so as to get praise from the jury even though he previously had difficulty in dividing time between study and work.Key Words: physiological needs, security needs, love and presence needs, appreciation needs, and self-actualization needs.